1999
DOI: 10.1200/jco.1999.17.10.3110
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of a Slow-Release Versus a Standard Formulation of Cytarabine for the Intrathecal Treatment of Lymphomatous Meningitis

Abstract: DepoCyt injected once every 2 weeks produced a high response rate and a better quality of life as measured by Karnofsky score relative to that produced by free ara-C injected twice a week.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
224
0
10

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 372 publications
(239 citation statements)
references
References 15 publications
5
224
0
10
Order By: Relevance
“…Liposomal cytarabine has been used only in the therapeutic setting both for HIV 31 and in the general population. [24][25][26][27][28][29][30] In particular, the only study of the treatment of lymphomatous meningitis in 5 patients with HIV-NHL showed a 60% CR rate. 31 There is only limited experience in the prophylactic setting in patients with aggressive lymphoma in the general population, whereas some data have been published in patients with acute lymphocytic or myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Liposomal cytarabine has been used only in the therapeutic setting both for HIV 31 and in the general population. [24][25][26][27][28][29][30] In particular, the only study of the treatment of lymphomatous meningitis in 5 patients with HIV-NHL showed a 60% CR rate. 31 There is only limited experience in the prophylactic setting in patients with aggressive lymphoma in the general population, whereas some data have been published in patients with acute lymphocytic or myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…Liposomal cytarabine was administered at the standard dose of 50 mg [24][25][26][27][28][29][30][31] by lumbar sac injection on Day 1 of the systemic treatment. The use of intrathecal steroids was not allowed.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Methotrexate (MTX) and liposomal cytarabine are the most frequently used agents for IC of LM from solid tumors. Liposomal cytarabine showed a better neurological progression‐free survival and a better impact on the quality of life 15, 16, 17. Nevertheless, all of the included subjects were suffered from lymphoma in these studies except one17 including patients with breast cancer, lung cancer, melanoma, primary brain tumor and other conditions.…”
mentioning
confidence: 98%